Implementation of the Muraja’ah Method (Tahfidz Partner) in Improving the Quality of Students’ Qur’an Memorization at Rumah Tahfidz Asy-Syifaa in Indonesia - Kholifah, Rosmaya; S, Hafiq (POTENSIA: Jurnal Kependidikan Islam, 2026)
The objectives of this study are: (1) to determine the quality of the students’ Qur’an memorization; (2) to examine the implementation of the muraja’ah tahfidz partner method in improving the quality of Qur’an memorization among students at Rumah Tahfidz Asy-Syifaa; and (3) to analyze and understand the supporting and inhibiting factors experienced by students in implementing the muraja’ah tahfidz partner method to enhance the quality of their Qur’an memorization. This research employs a qualitative approach using a descriptive case study design. Data were collected through observation, interviews, and documentation. The data analysis techniques included data reduction, data presentation, and data verification. The findings of the study can be summarized as follows: (1) The quality of memorization among the students at Rumah Tahfidz Asy-Syifaa can be categorized as good based on several predetermined indicators. This is further supported by the results of weekly evaluations. (2) The implementation of the muraja’ah tahfidz partner method at Rumah Tahfidz Asy-Syifaa is carried out through several stages, namely the preparation stage, the implementation stage, and the repetition/reinforcement stage. (3) The supporting factors in the implementation of the muraja’ah tahfidz partner method at Rumah Tahfidz Asy-Syifaa include structured and supervised muraja’ah activities as well as a conducive learning environment. Meanwhile, the inhibiting factors include feelings of laziness, poor time management, and the tendency for memorized verses to be easily forgotten.